2020
DOI: 10.1142/s0218271820500819
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and reentrant phase transition for logarithmic nonlinear charged black holes in massive gravity

Abstract: We investigate a new class of [Formula: see text]-dimensional topological black hole solutions in the context of massive gravity and in the presence of logarithmic nonlinear electrodynamics. Exploring higher-dimensional solutions in massive gravity coupled to nonlinear electrodynamics is motivated by holographic hypothesis as well as string theory. We first construct exact solutions of the field equations and then explore the behavior of the metric functions for different values of the model parameters. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This is the significant difference that the Van der Waals-like phase transition was usually only recovered in a variety of spherical horizon black hole backgrounds. Subsequently, the abundant thermodynamical behaviors of the black holes in dRGT massive gravity were investigated, such as the reentrant phase transitions, tricritical point [81][82][83][84]. It is also suggested that the phase transition of the dRGT black holes could relate to the Quasinormal mode [85,86] and the holographic entanglement entropy [87].…”
Section: Introductionmentioning
confidence: 99%
“…This is the significant difference that the Van der Waals-like phase transition was usually only recovered in a variety of spherical horizon black hole backgrounds. Subsequently, the abundant thermodynamical behaviors of the black holes in dRGT massive gravity were investigated, such as the reentrant phase transitions, tricritical point [81][82][83][84]. It is also suggested that the phase transition of the dRGT black holes could relate to the Quasinormal mode [85,86] and the holographic entanglement entropy [87].…”
Section: Introductionmentioning
confidence: 99%
“…Also, we fixed the minimum value of the BH mass that occurred at the degenerate horizon. We have also studied the thermal phase transitions and showed, in the linear electrodynamics case, i.e., ǫ = 0, the temperature became negative when r h < r d and therefore, heat capacity became negative and thus we have unstable BH [102][103][104][105]. The same conclusions can be applied to the NED case.…”
Section: Discussionmentioning
confidence: 55%
“…The 4-dimensional action of non-abelian logarithmic gauge theory with negative cosmological constant is [32], [33],…”
Section: Ads Black Brane Coupled To Non-abelian Logarithmic Gauge The...mentioning
confidence: 99%
“…x in Eq. ( 22) and variation with respect to Ã(3) ∞ , Green's function can be read as, G (33) xx (ω, 0) =…”
Section: Color Non-abelian DC Conductivitymentioning
confidence: 99%